P187 Pre-defined Gene Co-expression Modules in Rheumatoid Arthritis Transition towards Molecular Health following Tumour Necrosis Factor Inhibitor Therapy. (23rd April 2022) - Sutcliffe, Megan A; Nair, Nisha; Oliver, James; Morgan, Ann; Isaacs, John; Wilson, Gerry; Verstappen, Suzanne; Viatte, Sebastien; Hyrich, Kimme; Morris, Andrew; Barton, Anne; Plant, Darren
Abstract: Background/Aims: Tumour necrosis factor inhibitors (TNFi) have advanced the clinical management of rheumatoid arthritis (RA); however, only 30-40% of patients who receive initial treatment with a TNFi experience a beneficial response. The discovery of biomarkers of TNFi response would facilitate improved response rates and more objective monitoring of inflammation. Gene transcript levels measured in the blood of RA patients represent an attractive source of biomarkers. For example, a study by Oswald et al demonstrated reproducible changes in gene expression modules in RA patients treated effectively with a TNFi. Such gene modules were previously defined by Chaussabel et al following the assessment of gene co-expression patterns, transcript clustering patterns and functional associations amongst transcripts from several inflammatory diseases. We aim to replicate the changes in modular gene co-expression reported to occur in response to TNFi therapy in RA in a UK cohort described by Oswald et al; to test if changes in modular expression are specific to TNFi therapy by analysing change in gene co-expression in response to methotrexate (MTX); and to determine if module expression transitions towards a disease-free state in responding patients. Methods: Published whole blood transcriptomic data from disease-free controls (n = 10) and RA patients treated with either the TNFi adalimumab (n = 70) or MTX (n = 85) were studied. Transcriptomic data were available at pre-treatment and at 3-months (TNFi) and 4-weeks (MTX) post-treatment. Response to treatment was assessed using the EULAR response criteria following 3/6-months on-drug. For each of the 27 modules, the fraction of probes that significantly (p < 0.05) changed in expression between time-points was recorded. Linear mixed models were used to test if module expression transitioned towards a disease-free state following treatment. Results: In the TNFi cohort, 25 of the 27 modules significantly changed in expression between pre- and post-treatment, replicating published findings by Oswald et al. Six of these 27 modules transitioned towards a disease-free state by 3-months. Transition in module expression was irrespective of treatment response in 5 of the 6 modules, however one module (module 3.2) appeared to be dependent on good response to adalimumab. This module was linked to pathways of inflammation and TNF signalling. Similar patterns of modular expression changes were observed in the MTX cohort, but with reduced significance compared to TNFi treated patients. Conclusion: This study provides independent replication of changes in modular gene expression in TNFi treated RA patients. Gene expression changes were observed regardless of treatment response and were not specific to TNFi therapy. These results suggest that some factors of biological response are not detected by clinical classifiers of treatment response. Further research is now needed to test the utility of gene modules for prediction of clinical response, or for objective monitoring of molecular pathways that are responsive to treatment. Disclosure: M.A. Sutcliffe: None. N. Nair: None. J. Oliver: None. A. Morgan: None. J. Isaacs: None. G. Wilson: None. S. Verstappen: None. S. Viatte: None. K. Hyrich: None. A. Morris: None. A. Barton: None. D. Plant: None.